Structural Analysis, Radicalism Representation, and Moral Values in The Short Story "Kesunyian ini, Kambing Sekali Rasanya" (This Silence, such a Goat) By Eko Triono - Yanuanita Widiyaningrum; Else Liliani (Journal of Social Science, 2023)
This study aims to (1) describe the integration between the intrinsic elements of the short story "Kesunyian Ini, Kambing Sekali Rasanya" (This Silence, such a Goat) by Eko Triono using a structural method, and (2) describe the representation of radicalism and moral values ​​contained in the short story. This short story was researched through the steps of data collection; (1) reading the short story This Silence, Kambing Once It feels intensively, (2) analyzing the integration between the intrinsic elements of the short story and describing it, then (3) analyzing the elements of radicalism and morals that the author wants to convey in the short story and describing it. After going through the research process of structural analysis, representation of radicalism, and moral values, it can be seen that Eko Triono's efforts to combine the intrinsic elements of the short story well, so that the representation of radicalism and the message of moral values ​​contained in the short story can reach the reader.